2016
DOI: 10.1021/acs.jpcc.6b10812
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Perturbation: Role of Vacancy-Induced Localized Phonon States in Thermal Transport of Monolayer MoS2

Abstract: Sulfur vacancies in monolayer MoS2 can provide unexpected opportunities for tailoring the properties and device applications via defect engineering. However, determining the effect of vacancies in thermal transport remains a big challenge. Using a first-principles supercell approach, we reveal the dominant role of defect-induced quasi-localized phonon states in reducing thermal conductivity of MoS2. These states are related to flattened dispersions in phonon spectrum, which comes from perturbations in atomic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 88 publications
1
31
0
Order By: Relevance
“…Generally, the a transport direction with higher κ L is preferred in nanoelectronics, while the b direction is preferred in thermoelectric devices. For monolayer black phosphorus, the κ L along the a direction is comparable to that for the perfect monolayer MoS 2 using the same approach 121,122 , indicating efficient heat dissipation; along the b direction, the κ L is even For α-arsenene, the κ L along the a direction is similar to that for low-buckled silicene (28.3 W/mK) 123 . As noted in our previous study, by adding Si adatoms, the κ L of silicene can be reduced to 2.86 W/mK after the dumbbell structure is formed 36 .…”
Section: Lattice Thermal Conductivitymentioning
confidence: 77%
“…Generally, the a transport direction with higher κ L is preferred in nanoelectronics, while the b direction is preferred in thermoelectric devices. For monolayer black phosphorus, the κ L along the a direction is comparable to that for the perfect monolayer MoS 2 using the same approach 121,122 , indicating efficient heat dissipation; along the b direction, the κ L is even For α-arsenene, the κ L along the a direction is similar to that for low-buckled silicene (28.3 W/mK) 123 . As noted in our previous study, by adding Si adatoms, the κ L of silicene can be reduced to 2.86 W/mK after the dumbbell structure is formed 36 .…”
Section: Lattice Thermal Conductivitymentioning
confidence: 77%
“…33 Such defects induce the localization of phonon modes and a reduction of thermal conductivity due to an enhancement in Umklapp scattering. 34,35 Furthermore, first principle studies have pointed out that the zT may be as high as 6.24 for MoS 2 with S defects at room temperature. 36 The understanding of the interplay between Umklapp processes and defect scattering is still an open and complex issue that implies a realistic treatment of the disordering and thus of the Anderson localization phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Such correlation is paramount for understanding transport physics in such 2D systems as it is evident by the many papers reporting on their electrical and optical properties where intrinsic structural defects and their effects on transport mechanism cannot be ignored . On the other hand, in the recent years an increasing number of atomistic calculations have been done to theoretically predict the thermal conductivity of the MoS 2 monolayer and a wide range of thermal conductivity at room temperature, that is, κ = 23.2–155 W m −1 K −1 has been reported . Moreover, it was demonstrated theoretically that defects such as vacancies and isotopes suppress the thermal conductivity of monolayer MoS 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, molecular dynamic (MD) simulations showed that introducing vacancies to the lattice structure of MoS 2 keeps phonon specific heat and group velocity almost unchanged but decreases phonon relaxation time compared to its pristine form. Calculation based on first‐principles revealed that phonon group velocities are significantly lower near the vacancy‐induced quasi‐localized phonon modes. Also, isotopes were found to strongly scatter phonons with intermediate frequencies in the large‐size MoS 2 samples where boundary scattering has a minor effect .…”
Section: Introductionmentioning
confidence: 99%